Pengembangan Konsep Smart Government (Pemerintahan yang cerdas) di Kelurahan Sindangsari Kecamatan Pasarkemis Kabupaten Tangerang - Aprilianti, Baby Novega; Yusuf, Yusmedi; Suherman, Agus (Jurnal EMT KITA, 2024)
This research discusses the development of the Smart Government concept. It can be observed that Smart Government represents the advancement of governance concepts to provide solutions to problems in rural areas. This research uses descriptive qualitative methods. Data collection techniques include interviews, observation, and documentation. Data analysis techniques in this study are: data collection, data reduction, data presentation, and conclusion drawing. The purpose of this research is to examine the development of the smart government concept in Sindangsari Village, identify the obstacles encountered in its development, and explore efforts to overcome them. The results of this study are evaluated using three key indicators of smart government as outlined by Cohen (2014) in Santoso & Rahmadanita (2020): Online Service, Infrastructure, and Open Government. The findings show that the smart government concept in Sindangsari Village has produced favorable results for the Online Service indicator, while the Infrastructure and Open Government indicators are less optimal due to limited budget resources and human capital, which hinders the village's capacity to provide information and communication technology-based services. Therefore, improvements in both indicators are necessary.